Thermal Injuries Caused by Water from Loose Garden Hoses - Karolína Uhrová Bc. of science; Pavel Böhm PhD Student (SAGE Publishing, 2021)
This is a monitoring research, the purpose of which is to point out the danger of scalding with water from loose garden hoses. All the stated data are the result of this research, which occurred during the month of August. To adequately compare the maximum temperature that the water reaches in garden hoses exposed to sunlight, 2 different surfaces were chosen, namely grass and concrete. It has been found that water in garden hoses, which lie in a place exposed to sunlight, is able to reach temperatures at which, in case of contact with human skin, there is a risk of scalding. The results confirmed the assumption that the temperature in the grass will be lower in the hoses than in the concrete surface. At an air temperature of 35°C, the water in the hoses on the grass reached a temperature of up to 47.3°C. On a concrete surface at an air temperature of 28.5°C, the water in the hoses reached 49.8°C. There is a risk of scalding from such hot water contact with the skin, and especially with sensitive baby skin. The aim of this research is to provide valid data on the risk of spilling hyperthermic water in free-lying garden hoses exposed to sunlight. The threat of scalding can occur unknowingly or through negligence, the risk of scalding with such water increases during tropical days significantly.